2002
DOI: 10.1021/cm020949f
|View full text |Cite
|
Sign up to set email alerts
|

Organic Field-Effect Transistor Using Oligoselenophene as an Active Layer

Abstract: Thiophene oligomers and polymers are promising compounds applicable to organic field-effect transistors 1 (OFETs), photodiodes, 2 light-emitting diodes, 3 and their integrated devices. 4 Selenophene is a homologue of the chalcogenophenes and the chemical and physical properties are similar to those of thiophene. To our knowledge, however, there has been no report on organic devices made with oligo-or polyselenophenes. This may be ascribable to the poor electrical properties of the polyselenophenes reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 20 publications
3
62
0
Order By: Relevance
“…[11][12][13][14][15] Although the synthesis of several oligoselenophenes has been reported, oligoselenophenes in general have been scantly studied, especially when compared with at least one thousand papers on their oligothiophene analogues. [16,17] 2,2':5',2'':5'',2'''-Quaterselenophenes (4 Se) [17] have been used as active semiconductors in organic fieldeffect transistors (OFET). Selenophene-containing oligomers have attracted great interest as OFET materials [18,19] Abstract: Recently, a family of conducting polyselenophenes was synthesized, and they were shown to have a number of interesting properties.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Although the synthesis of several oligoselenophenes has been reported, oligoselenophenes in general have been scantly studied, especially when compared with at least one thousand papers on their oligothiophene analogues. [16,17] 2,2':5',2'':5'',2'''-Quaterselenophenes (4 Se) [17] have been used as active semiconductors in organic fieldeffect transistors (OFET). Selenophene-containing oligomers have attracted great interest as OFET materials [18,19] Abstract: Recently, a family of conducting polyselenophenes was synthesized, and they were shown to have a number of interesting properties.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Other types of conjugated systems have also exhibited high mobilities in FET devices. [4,20] 2,2':5',2'':5'',2'''-Quaterselenophene (4Se) [21] and selenophene-containing oligomers [22,23] have been used as active semiconductors in OFETs. Selenium-containing oligomers have attracted great interest as OFET materials [23] since Takimiya et al [22] reported higher hole mobilities for selenium-containing compounds compared to the corresponding sulfur analogues.…”
mentioning
confidence: 99%
“…Compound 2 shows increasing performance with increasing the deposition temperature, and exhibits a mobility of 2.8 × 10 −3 cm 2 V −1 s −1 for a thin film deposited at 60 °C (Figure 5a,b). This is due to the increasing grain size and the decreasing number of grain boundaries [36,37], as observed in AFM and XRD. After 30 days, the device shows reduced carrier mobility by two orders of magnitude, though the unsubstituted pentacene does not show transistor properties at all after this period.…”
Section: Transistor Propzertiesmentioning
confidence: 76%